PENGARUH STRATEGI BAURAN PEMASARAN TERHADAP KEPUASAN KONSUMEN PADA AROMA BAKERY & CAKE MEDAN - Sarah Nabilah; Adelina Lubis; Eka Dewi Setia Tarigan (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2020)
The research entitled The Effect of Marketing Mix Strategy on Customer Satisfaction at Aroma Bakery Cake Medan aims to provide empirical evidence about the effect of simultaneous and partial price, product, location and promotion variables on customer satisfaction at Aroma Bakery Cake Medan, and knowing promotion variables dominant influence on customer satisfaction at Aroma Bakery Cake Medan.The data used in this study are primary data obtained through the distribution of questionnaires to respondents, namely consumers of Aroma Bakery Cake Medan. The sampling technique used is random sampling. For data analysis, the author uses multiple linear analysis Based on the results of testing the hypothesis it can be announced that product variables, location and promotion are positively and significantly related, but the price variable is not positive and not significant positive partial to customer satisfaction at Aroma Bakery Cake Medan. Taken together / simultaneous product variables, prices, locations and promotions show a positive and significant impact on customer satisfaction on Aroma Bakery Cake Medan. In addition, the test results also state that the dominant variables affecting consumers on the Aroma Bread Cake Medan are promotion variables.